Synthesis, crystal structure, and spectroscopic characterization of a new non-centrosymmetric compound, 1-(2-chloroquinolin-3-yl)-N-(4-fluorobenzyl)methanimine - Hachicha, Maha; Nasri, Rawia; Zid, Mohamed Faouzi; Mrabet, Hedi (European Journal of Chemistry, 2024)
In this work, we report the synthesis and characterization of a new condensed aromatic heterocycle (1-(2-chloroquinolin-3-yl)-N-(4-fluorobenzyl)methanimine) useful in various fields, mainly in medicinal and therapeutic chemistry, with interesting biological properties. Characterization of the title compound was carried out by 1H, 13C, 19F nuclear magnetic resonance and X-ray diffraction techniques. The crystal structure reveals that title compound crystallizes in the monoclinic system and crystal data for C17H12ClFN2: monoclinic, space group P21 (no. 4), a = 7.2253(10) Å, b = 5.7720(10) Å, c = 17.105(2) Å, β = 95.338(10)°, V = 710.26(18) Å3, Z = 2, T = 298(2) K, μ(MoKα) = 0.274 mm-1, Dcalc = 1.397 g/cm3, 5010 reflections measured (4.784° ≤ 2Θ ≤ 54.324°), 3160 unique (Rint = 0.0501, Rsigma = 0.0506) which were used in all calculations. The final R1 was 0.0339 (I > 2σ(I)) and wR2 was 0.0907 (all data). The obtained molecular structure has an antiparallel arrangement of the molecular unit leading to a one-dimensional framework.